Hubungan Penggunaan Depo Medroxy Progesterone Acetate (DMPA) Jangka Panjang Terhadap Perubahan Tekanan Darah Wanita Usia Subur Di RSIA Masyita Makassar - Nurlina Akbar (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Depo Medroxy Progesterone Acetate (DMPA) contraceptive if used long-term is known cause an increase in blood pressure. However, the mechanism of the relationship between DMPA and blood pressure changes in fertile women also unclear. Therefore, this study aims to determine the relationship between long-term use of DMPA and increased blood pressure in fertile women. This research was an analytical survey research with a case control study approached where this research was conducted by measuring the blood pressure of the sample first and then tracing the results of his blood pressure measurement retrospectively while being DMPA injection acceptor. This research was conducted at RSIA Masyita Makassar. The data obtained will be analyzed by using chi-square test. The results of the analysis between longtime of DMPA contraception used and blood pressure increased at the acceptors were significant (p=0.005). This can be seen in the case group who in blood pressure using DMPA> 2 years as many as 15 people (71.4%) while in the control group only 5 people (23.8%). Meanwhile, the control group who had normal blood pressure and used DMPA